Cultural Heritage Infrastructures in Digital Humanities - Benardou, Agiatis (Routledge, 2018)
In this book, authors from a wide range of countries, representing some of the best research projects in digital humanities related to cultural heritage, discuss their latest findings, both in terms of new tools and archives, and how they are used (or not used) by both specialists and by the general public.